Melodies Unheard Essays on the Mysteries of Poetry - Hecht, Anthony (Johns Hopkins University Press, 2020)
Originally published in 2003. The fruit of a lifetime's reading and thinking about literature, its delights and its responsibilities, this book by acclaimed poet and critic Anthony Hecht explores the mysteries of poetry, offering profound insight into poetic form, meter, rhyme, and meaning. Ranging from Renaissance to contemporary poets, Hecht considers the work of Shakespeare, Sidney, and Noel; Housman, Hopkins, Eliot, and Auden; Frost, Bishop, and Wilbur; Amichai, Simic, and Heaney. Stepping back from individual poets, Hecht muses on rhyme and on meter, and also discusses St. Paul's Epistle to the Galatians and Melville's Moby-Dick. Uniting these diverse subjects is Hecht's preoccupation with the careful deployment of words, the richness and versatility of language and of those who use it well.Elegantly written, deeply informed, and intellectually playful, Melodies Unheard confirms Anthony Hecht's reputation as one of our most original and imaginative thinkers on the literary arts.